2014
DOI: 10.3389/fpls.2014.00341
|View full text |Cite
|
Sign up to set email alerts
|

The alternative Medicago truncatula defense proteome of ROS—defective transgenic roots during early microbial infection

Abstract: ROP-type GTPases of plants function as molecular switches within elementary signal transduction pathways such as the regulation of ROS synthesis via activation of NADPH oxidases (RBOH-respiratory burst oxidase homolog in plants). Previously, we reported that silencing of the Medicago truncatula GTPase MtROP9 led to reduced ROS production and suppressed induction of ROS-related enzymes in transgenic roots (MtROP9i) infected with pathogenic (Aphanomyces euteiches) and symbiotic microorganisms (Glomus intraradice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…And in our study the total iron content of roots and leaves in both mutant and ROP6-overexpressed plants were not significantly changed compared with WT, but the downward trend of active iron content of leaves in the rop6 mutant showed that AtROP6 or ROS may be involved in iron distribution from roots to shoots. Furthermore, the silencing of the Medicago truncatula GTPase MtROP9 led to reduced ROS production while it suppressed induction of ROS-related enzymes [51]. These observations are consistent with our own observation of a markedly decreased accumulation of ROS and H 2 O 2 under Fe starvation in the rop6 mutant (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…And in our study the total iron content of roots and leaves in both mutant and ROP6-overexpressed plants were not significantly changed compared with WT, but the downward trend of active iron content of leaves in the rop6 mutant showed that AtROP6 or ROS may be involved in iron distribution from roots to shoots. Furthermore, the silencing of the Medicago truncatula GTPase MtROP9 led to reduced ROS production while it suppressed induction of ROS-related enzymes [51]. These observations are consistent with our own observation of a markedly decreased accumulation of ROS and H 2 O 2 under Fe starvation in the rop6 mutant (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…From 14 transcripts matching MLPs, 11 were consistently repressed (Supplementary Figure S5V). Although the function of these proteins has not been completely elucidated, there is evidence of their regulation through hormone signaling (Ruperti et al, 2002; Yang et al, 2015; Wang et al, 2016), and activation in response to pathogens (Schenk et al, 2000; Kiirika et al, 2014; Yang et al, 2015). However, our results were opposite to these studies and we found only one study were 16 major latex proteins were repressed in response to oxidative stress in Arabidopsis (Stanley Kim et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…We found that several transcripts associated with ABA synthesis, degradation and signal transduction were also up-regulated in DVI, which indicated their key roles in chickpea defense. Transcripts for several pathogenesis related proteins, Major latex proteins 40 , auxin binding proteins 41 , etc. from ‘biotic and abiotic stress response’ category were detected with higher abundance and elevated expression in DVI.…”
Section: Discussionmentioning
confidence: 99%